2020
DOI: 10.3389/fmicb.2020.01470
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Neuronal Culture for Viral Transport Research

Abstract: Neuron-invading viruses usually enter via the peripheral organs/tissues of their mammalian hosts and are transported to the neurons. Virus trafficking is critical for transport or spread within the nervous system. Primary culture of neurons is a valuable and indispensable method for neurobiological research, allowing researchers to investigate basic mechanisms of diverse neuronal functions as well as retrograde and anterograde virus transport in neuronal axons. Primary ganglion sensory neurons from mice can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…In a study by Smith, freshly produced green fluorescent protein (GFP)-tagged capsids were observed to traverse monomeric red fluorescent protein-tagged capsids in opposite directions within the same axon ( Smith et al, 2004 ). Therefore, the regulation of transport direction and the resulting coordination of movement occur at the level of individual capsids rather than through the overarching control of axonal transport ( Wang et al, 2020 ).…”
Section: The Models For Studying Latent Infections Of Alphaherpesvirusesmentioning
confidence: 99%
“…In a study by Smith, freshly produced green fluorescent protein (GFP)-tagged capsids were observed to traverse monomeric red fluorescent protein-tagged capsids in opposite directions within the same axon ( Smith et al, 2004 ). Therefore, the regulation of transport direction and the resulting coordination of movement occur at the level of individual capsids rather than through the overarching control of axonal transport ( Wang et al, 2020 ).…”
Section: The Models For Studying Latent Infections Of Alphaherpesvirusesmentioning
confidence: 99%
“…In the alpha herpesvirus literature, this problem has led to great confusion over the relationship between finalassembly/envelopment and axonal transport of virus particles [16]: do non-enveloped particles in axons represent progeny particles that are not yet enveloped, or inoculum particles that have already shed their envelopes during entry? Campenot trichambers, like related microfluidics devices [17][18][19], are an important tool to clarify this problem of distinguishing virus inoculum and viral progeny (see Note 1). These compartmented neuron culture devices allow SCG and DRG neurons to extend axons between chambers, while maintaining fluidic separation between the chambers [20].…”
Section: Introductionmentioning
confidence: 99%